Assessment of Brown Color as an Indicator of Salty and Bitter Taste Perception: a Case of Reduced- and Low-sodium Barbecue Sauces - Alonso, Jose Ramon; Sriwattana, Sujinda; Chaiya, Busarawan; Prinyawiwatkul, Witoon (Progress in Applied Science and Technology, 2026)
Color cue influences taste expectation. This study evaluated brown color as indices for salty and bitter tastes of reduced- and low-sodium barbecue sauces formulated with eight salt mixtures [10-60% NaCl: 30-60% KCl: 0-40% Glycine]. 240 consumers rated salty and bitter tastes based on brown color (expectation), then rated actual taste of the samples. The highest total color difference value was 2.12 (<2.3 for “just-noticeable-difference”), hence the color among treatments was presumed to be undifferentiated by the consumers. Six samples containing 20-50% NaCl; 30-60% KCl; 0-40% Glycine showed congruent saltiness expectation and actual salty taste perception [P>0.05, the Cochran-Mantel-Hansel test]; however, samples with 60%:40%:0% and/or 10%:60%:30% were incongruent in such association. Sample containing 10:60:30 was tasted less salty than expected (P=0.002). Congruent bitterness evoked by brown color (L*=47.6-48.3, a*=1.6-3.0, b*=2.6-3.6) and actual taste was observed for all samples. This study demonstrated that brown color may be used as an indicator for salty and bitter taste of barbecue sauces.